Developing, purchasing, implementing and monitoring AI tools in radiology: practical considerations. A multi-society statement from the ACR, CAR, ESR, RANZCR & RSNA. - Brady, Adrian P; Allen, Bibb.; Chong, Jaron.; Kotter, Elmar.; Kottler, Nina.; Mongan, John.; Oakden-Rayner, Lauren.; Santos, Daniel Pinto.; Tang, An.; Wald, Christoph.; Slavotinek, John. (Tufts University. Tisch Library., 2024)
Keywords: Artificial Intelligence, Radiology, Automation, Machine learning.; Springer Open.